The effects of verbal cueing for high intended movement velocity on power, neuromuscular activation, and performance. (27th February 2021) - Rheese, Michael; Drinkwater, Eric J.; Leung, Hans; Andrushko, Justin W.; Tober, Jacob; Hendy, Ashlee M.
Abstract : It is widely believed that lifting heavy loads slowly, but with a conscious intention to move at high velocity, can produce resistance training (RT) adaptations indicative of rapid movements. This study investigated the effects of verbally cued high "intended" movement velocity (HIMV) during RT on neuromuscular and performance outcomes. 20 untrained volunteers (aged 24.2 ± 3.9 years) participated in 3 weeks of knee extension training. Participants were randomly allocated to receive verbal cues focusing on high intended movement velocity, HIMV, or steady and controlled movement, TRAD (traditional training). All other training variables, including actual movement velocity (30° s −1 ), remained constant. Increase in mean power output at 30° s −1 was greater for TRAD than HIMV (76% and 33%, respectively, P = 0.027). There were main effects for time (but no between‐group differences) for maximal isometric force (+14%, P = 0.003), peak torque at 180° s −1 (+22%, P = 0.006), peak torque at 30° s −1 (+29%, P < 0.001), 3‐repetition maximum (+20%, P < 0.001), and resting corticospinal excitability (+43%, P = 0.017). There were no differences between groups or across time for voluntary activation ( P = 0.793), spinal excitability ( P = 0.686), or intracortical inhibition (all P > 0.05). HIMV verbal cueing did not produce additional neurophysiological or performance benefits when compared to traditional cueing. Overall, our results demonstrated that verbal cueing did not alter the principle of velocity‐specific adaptation. Cueing that increases the duration of maximal effort may be optimal for maximizing average power output at low speeds.